Space Use in the Commons: Evaluating a Flexible Library Environment - Asher, Andrew D. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – This article evaluates the usage and user experience of the Herman B Wells Library’s Learning Commons, a newly renovated technology and learning centre that provides services and spaces tailored to undergraduates’ academic needs at Indiana University Bloomington (IUB).Methods – A mixed-method research protocol combining time-lapse photography, unobtrusive observation, and random-sample surveys was employed to construct and visualize a representative usage and activity profile for the Learning Commons space.Results – Usage of the Learning Commons by particular student groups varied considerably from expectations based on student enrollments. In particular, business, first and second year students, and international students used the Learning Commons to a higher degree than expected, while humanities students used it to a much lower degree. While users were satisfied with the services provided and the overall atmosphere of the space, they also experienced the negative effects of insufficient space and facilities due to the space often operating at or near its capacity. Demand for collaboration rooms and computer workstations was particularly high, while additional evidence suggests that the Learning Commons furniture mix may not adequately match users’ needs.Conclusions – This study presents a unique approach to space use evaluation that enables researchers to collect and visualize representative observational data. This study demonstrates a model for quickly and reliably assessing space use for open-plan and learning-centred academic environments and for evaluating how well these learning spaces fulfill their institutional mission.